Global Banks' Dollar Funding : A Source of Financial Vulnerability - Barajas, Adolfo (IMF Working Papers; Working Paper ;, 2020)
Leading up to the global financial crisis, US dollar activity by global banks headquartered outside the United States played a crucial role in transmitting shocks originating in funding markets. Although post-crisis regulation has improved banking systems' resilience, US dollar funding remains a global vulnerability, as evidenced by strains that reemerged in March 2020 in the midst of the COVID-19 crisis. We show that shocks to US dollar funding costs lead to financial stress in the home economies of these global non-US banks, and to spillovers to borrowers, especially emerging economies. US dollar funding vulnerability amplifies these negative effects, while some policy-related factors act as mitigators, such as swap line arrangements between central banks and international reserve holdings. Thus, these vulnerabilities should be monitored and, to the extent possible, controlled.